2005
DOI: 10.1164/rccm.200505-767oc
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Surfactant Protein D Content Modulates Bleomycin-induced Lung Injury

Abstract: These data provide new in vivo evidence for an antiinflammatory role for SP-D in response to noninfectious, subacute lung injury via modulation of oxidative-nitrative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 57 publications
(76 reference statements)
5
58
0
Order By: Relevance
“…In SP-D Ϫ/Ϫ mice, we showed increased susceptibility to bleomycin and evidence of oxidative-nitrative stress (17). Similar findings were observed when the same mice were infected with Pneumocystis carinii (6).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In SP-D Ϫ/Ϫ mice, we showed increased susceptibility to bleomycin and evidence of oxidative-nitrative stress (17). Similar findings were observed when the same mice were infected with Pneumocystis carinii (6).…”
supporting
confidence: 84%
“…It is upregulated in a variety of inflammatory and infectious conditions including Pneumocystis pneumonia (5), asthma (2), and bleomycin injury (17). Mice or rats exposed to hyperoxic challenge also have increases in SP-D (13), suggesting that it may have a role in protection from this insult.…”
mentioning
confidence: 99%
“…We have previously shown that SP-D null mice demonstrate enhanced susceptibility to intratracheal administration of bleomycin, whereas SP-D overexpressing mice were protected (14). Based on these results and on data showing increased oxidative stress in SP-D null mice, we hypothesized a protective role for SP-D in hyperoxic lung injury.…”
mentioning
confidence: 86%
“…Mice overexpressing the rat isoform of SP-D (rSP-D) in a lung-specific fashion using the human 23.7 kb SP-C promoter on the Swiss Black (SWB) background (SP-D OE) were provided by Dr. Frank McCormack and have been described previously (14,20). Heterozygous transgenic mice carrying a single concatamer of the rSP-D transgene were crossed with wild-type SWB mice to generate SP-D OE mice and littermate control (wild-type [WT]) mice.…”
Section: Sp-d Oe Micementioning
confidence: 99%
See 1 more Smart Citation